Examination of Sex-Specific Participant Inclusion in Exercise Physiology Endothelial Function Research: A Systematic Review - Lew, Lindsay A.; Williams, Jennifer S.; Stone, Jenna C.; Au, Alicia K. W.; Pyke, Kyra E.; MacDonald, Maureen J. (Frontiers in Sports and Active Living, 2022)
Background: To combat historical underrepresentation of female participants in research, guidelines have been established to motivate equal participation by both sexes. However, the pervasiveness of female exclusion has not been examined in vascular exercise physiology research. The purpose of this study was to systematically quantify the sex-specific prevalence of human participants and identify the rationales for sex-specific inclusion/exclusion in research examining the impact of exercise on vascular endothelial function. Methods: A systematic search was conducted examining exercise/physical activity and vascular endothelial function, assessed via flow mediated dilation. Studies were categorized by sex: male-only, female-only, or mixed sex, including examination of the sample size of males and females. Analysis was performed examining sex-inclusion criteria in study design and reporting and rationale for inclusion/exclusion of participants on the basis of sex. Changes in proportion of female participants included in studies were examined over time in 5 year cohorts. Results: A total of 514 studies were identified, spanning 26 years (1996-2021). Of the total participants, 64% were male and 36% were female, and a male bias was identified (32% male-only versus 12% female-only studies). Proportions of female participants in studies remained relatively constant in the last 20 years. Male-only studies were less likely to report sex in the title compared to female-only studies (27% versus 78%, p<0.001), report sex in the abstract (72% versus 98%, p<0.001) and justify exclusion on the basis of sex (15% versus 55%, p<0.001). Further, male-only studies were more likely to be conducted in healthy populations compared to female-only studies (p=0.002). Qualitative analysis of justifications identified four themes: sex-specific rationale or gap in the literature, exclusion of females based on the hormonal cycle or sex-differences, maintaining congruence with the male norm, and challenges with recruitment, retention and resources. Conclusions: This systematic review provides the first analysis of sex-based inclusion/exclusion and rationale for sex-based decisions in human vascular exercise physiology research. These findings contribute to identifying the impact of research guidelines regarding inclusion of males and females and the perceived barriers to designing studies with equal sex participation, in an effort to increase female representation in vascular exercise physiology research.